Use of the Dynamic Indicators of Basic Early Literacy Skills with English Language Learners - McCarthy, Rachel (My University, 2011)
This study examined the the use of curriculum-based measures in reading with English Language Learners in the Eau Claire Area School District. It analyzed the predictive validity of the Dynamic Indicators of Basic Early Literacy Skills (DIBELS) measures for future performance on the state mandated third grade reading test in Wisconsin (Wisconsin Knowledge and Concepts Exam).
Color poster with text and tables.
Keywords: English language--Study and teaching--Foreign speakers; Reading--Ability testing--Evaluation; Dynamic Indicators of Basic Early Literacy Skills (DIBELS); Posters; Educational tests and measurements--Evaluation